Classification of maternal mortality by ICD-MM: a retrospective study from a tertiary care hospital of Chhattisgarh - Ekka, Anju R.; Jogi, Sangeeta R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Sustainable development goal 3 (SDG 3) includes an ambitious target of reducing the global maternal mortality rate (MMR) to less than 70 per 100 000 births by 2030. To reach this target, countries need an accurate picture of the levels and causes of maternal deaths. A standardization of the cause of death attribution will improve interpretation of data on maternal mortality, analysis on the causes of maternal death, and allocation of resources and programmes intended to address maternal mortality. International classification of diseases-maternal mortality (ICD-MM) has proven to be easily applicable and helps clarify the cause of maternal death. Methods: Retrospective study of 142 maternal death cases was done in a tertiary medical centre (medical college) from December 2017 to November 2020 for determining the causes of maternal death and their classification according to ICD-MM. Results: Direct causes of maternal deaths were observed in 82.39% cases whereas indirect causes were present in remaining 17.61% cases. Hypertensive disorders (35.92%), obstetric haemorrhage (26.06%) and pregnancy related infection (14.79%) constituted the major groups of direct cause of maternal deaths whereas anaemia was the most common indirect cause (7.75%). Conclusions: Hypertensive disorders (35.92%), obstetric haemorrhage (26.06%) and pregnancy related infection (14.79%) were the major causes of direct obstetric death and anaemia (7.75%) was the most common cause of indirect obstetric death. All of these causes are preventable with targeted interventions. Reducing maternal mortality is one of the key targets within the SDG and ICD-MM is a valuable tool for uniform and standard classification of maternal deaths as well as for developing strategies for reducing maternal death. Training on cause of death certification, maternal death surveillance and response (MDSR) documentation and use of ICD is essential to enable consistent application of ICD coding and improve data collection and analysis.